Phylogenetic structure of Holbrookia lacerata (Cope 1880) (Squamata: Phrynosomatidae): one species or two? - Hibbitts, Toby J.; Ryberg, Wade A.; Harvey, Johanna A.; Voelker, Gary; Lawing, A. Michelle; Adams, Connor S.; Neuharth, Dalton B.; Dittmer, Drew E.; Duran, C. Michael; Wolaver, Brad D.; Pierre, Jon Paul; Labay, Benjamin J.; et al. (Zootaxa, 2019)
Species delimitation attempts to match species-level taxonomy with actual evolutionary lineages. Such taxonomic conclusions are typically, but not always, based on patterns of congruence across multiple data sources and methods of analyses. Here, we use this pluralistic approach to species delimitation to help resolve uncertainty in species boundaries of phrynosomatid sand lizards of the genus Holbrookia. Specifically, the Spot-tailed Earless Lizard (H. lacerata) was historically divided into a northern (H. l. lacerata) and southern (H. l. subcaudalis) subspecies based on differences in morphology and allopatry, but no research has been conducted evaluating genetic differences between these taxa. In this study, patterns in sequence data derived from two genes, one nuclear and one mitochondrial, for 66 individuals sampled across 18 counties in Texas revealed three strongly supported, reciprocally monophyletic lineages, each comprised of individuals from a single geographic region. Distinct genetic variation evident across two of these regions corresponds with differences in morphology, differences in environmental niche, and lines up with the presumed geographic barrier, the Balcones Escarpment, which is the historical subspecies boundary. The combined evidence from genetics, morphology and environmental niche is sufficient to consider these subspecies as distinct species with the lizards north of the Balcones Escarpment retaining the name Holbrookia lacerata, and those south of the Balcones Escarpment being designated as Holbrookia subcaudalis.